Promoter effect of microbes in slope eco-engineering: Effects on plant growth, soil quality and erosion rate at different vegetation densities - Normaniza, Osman; Halim, Aimee; Yusoff, Ismail; Tan, Geok Yuan Annie; Rozainah, Mohamad Zakaria (ALOKI Applied Ecological Research and Forensic Institute, 2018)
Slope revegetation is claimed to be accelerated with the right choice of plants and effective planting techniques for the root establishment. In addition, microorganisms also promote plant growth via nutrient intensification and soil-root enhancement, hence may alleviate soil surface erosion. Thus, this study is aimed to identify the effects of microbial application on plant growth, soil properties and soil erosion rate at different vegetation densities. Six experimental plots were set up at the Guthrie Corridor Expressway, Selangor, Malaysia, with different amount of microbial application and vegetation density. Dense vegetation cover with microbial application (DM) plot exhibited the highest soil microbes abundance and fungal/bacteria (F/B) ratio after 24 months of observation. Meanwhile, photosynthetic rate and root length density of Lantana camara in the DM plot revealed the highest rate, followed by Melastoma malabathricum and Bauhinia purpurea. Moreover, the soil of DM plot had also increased in CEC, total N, and respiration rate, reflecting the soil quality. Consequently, erosion rate of DM plot exhibited the 52.6% of total decrement from the initial experiment. Thus, microbes are proven to be relatively good promoters for the improvement of plant growth performance, the soil quality and alleviate the soil erosion of the slope.